Exclusion of Mediterranean ant species enhances biological control of the invasive mealybug Delottococcus aberiae in citrus - Plata, Ángel; Gómez-Martínez, María A.; Beitia, Francisco J.; Tena, Alejandro (Wiley Online Library, 2023)
Background: Delottococcus aberiae is an invasive mealybug that produces severe damage in Spanish citrus. This mealybug has established a mutualistic relationship with native Mediterranean ant species that may limit biological control of this pest. Herein, we evaluated the effect of tending ants on the biological control of D. aberiae. To do this, we compared: (I) the density of D. aberiae, (II) the density of its natural enemies, and (III) the damage produced by the mealybug in trees with (control) and without ants (ants excluded with sticky barriers) in two citrus orchards across two consecutive years. Results: Lasius grandis was the most abundant ant species in both orchards and represented more than 95% of the ants tending D. aberiae in control trees. Spiders and lacewings were the most abundant predators observed in mealybug colonies, and the exclusion of mutualistic ants increased their abundance. Moreover, in control trees, ant activity throughout the year was negatively correlated with the relative abundance of predators (number of predators per mealybug). No parasitoids were recovered during field experiments. Ant exclusion reduced the density of D. aberiae and the ratio of damaged fruit at harvest across years and orchards. Conclusions: This work corroborates the previous finding that D. aberiae benefits from its mutualistic relationship with L. grandis, probably because the presence of ants reduced the abundance of generalist predators. This mutualism can be disrupted using physical barriers on the trunk. Further research should assess other methods of ant control that are more economic and feasible for citrus producers.